Child Health in Five Early Medieval Irish Sites: A Multidisciplinary Approach. (4th September 2016) - Novak, M.; Howcroft, R.; Pinhasi, R.
Abstract: With the aim to reconstruct child health in five early medieval (5th–12th c. CE) Irish sites, an osteoarchaeological study of three biological stress indicators – cribra orbitalia, linear enamel hypoplasia (LEH) and periostitis – has been conducted on 229 skeletons. In addition, Irish early medieval written sources testifying on child health during this period were consulted. These data were furthermore combined with the results of stable isotope analyses (nitrogen and carbon) conducted on subadult bone specimens. Cribra orbitalia was found in 27.5% of the studied individuals (48.6% of subadults were affected), with only two cases active at the time of death. The prevalence of LEH per individual is 63.5% (78.9% in subadults and 59.7% in adults). The age ranges of LEH formation vary between 1.9 and 4.8 years for the maxillary teeth and between 1.8 and 6.2 years for the mandibular teeth. Periosteal inflammations were recorded in over one third of the studied subadults (36.2%) with six cases active at the time of death. The stable isotope results suggest a diet based on terrestrial food sources, with little or no marine input. The presented data strongly suggest that most of the individuals were exposed to a high level of physiological stress during their childhood, and as such does not support the so called 'osteological paradox' hypothesis. The observed disturbances were probably caused by a synergistic effect of various biological and socio‐cultural factors. Although the historical records indicate certain differences in diet and lifestyle between social classes and the sexes, this study showed that the children of all ages had poor health in all social classes across a wide geographical location for the full time period of the early medieval. Copyright © 2016 John Wiley & Sons, Ltd.